2016
DOI: 10.1016/j.cgh.2015.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Low Rates of Malignancy and Mortality in Asymptomatic Patients With Suspected Neoplastic Pancreatic Cysts Beyond 5 Years of Surveillance

Abstract: This article has an accompanying continuing medical education activity, also eligible for MOC credit, on page e67. Learning Objective-Upon completion of this activity, successful learners should be able to understand the prevalence of pancreatic cysts in clinical practice and determine the prognosis of asymptomatic pancreatic cysts. BACKGROUND & AIMS: The 2015 American Gastroenterological Association guidelines recommend discontinuation of surveillance of pancreatic cysts after 5 years, although there are limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 11 publications
4
29
0
Order By: Relevance
“…In 2015, a meta‐analysis was published including 2177 patients under surveillance for SB‐IPMN, of which only 82 (3.7%) developed a pancreatic malignancy . Since then, several additional studies, each including at least 300 patients with at least 5 years of follow‐up, reported a pancreatic cancer risk of only 0%‐1.6% for small asymptomatic cysts . However, all these studies were retrospective and the actual, long‐term risk is yet to be determined by large and prospective studies.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, a meta‐analysis was published including 2177 patients under surveillance for SB‐IPMN, of which only 82 (3.7%) developed a pancreatic malignancy . Since then, several additional studies, each including at least 300 patients with at least 5 years of follow‐up, reported a pancreatic cancer risk of only 0%‐1.6% for small asymptomatic cysts . However, all these studies were retrospective and the actual, long‐term risk is yet to be determined by large and prospective studies.…”
Section: Introductionmentioning
confidence: 99%
“…PCLs are detected in 1.9–2.1% of the patients on computed tomography (CT) and in 13.5–49.1% of the patients on magnetic resonance imaging, with the incidence increasing with age . Although various investigations into the progression rate and malignancy risk of PCLs have been previously reported, most studies only focused on definite or presumed branch duct intraductal papillary mucinous neoplasms (IPMNs). In clinical practice, the lesions we encounter are generally asymptomatic small PCLs, as opposed to definite neoplastic cystic lesions, such as IPMNs or mucinous cystic neoplasms.…”
Section: Introductionmentioning
confidence: 99%
“…These limitations, however, are unavoidable at present, due to the lack of a well‐characterised cohort of individuals with low‐risk IPMNs that is large enough, has sufficient follow‐up time, and has been followed according to a pre‐defined protocol. A negative prediction tool focuses on pancreatic cystic lesions at lowest risk of malignant progression, recently estimated to be 0%‐1.6% . Inherently, the number of patients who develop malignancy in this target group is extremely low.…”
mentioning
confidence: 99%